LANDRACES, UTILIZATION, AND MANAGEMENT OF BAMBOO IN SUKAMENAK VILLAGE, SUMEDANG, WEST JAVA - Johan Iskandar; Opan Suhendi Suwartapradja; Budiawati Supangkat Iskandar; Diana Budiyanti; Sidik Permana (Universitas Padjadjaran, 2022)
There are many species of bamboo a rural ecosystem of West Java, growing wild or being cultivated. Both bamboo species and bamboo gardens have various ecological, economic, and socio-cultural functions. However, many bamboo gardens in rural West Java have been converted to other land uses. Consequently, the reduction or loss of various ecological, economic and socio-cultural functions of bamboo. The purpose of this study was to assess the local knowledge of the rural people on the landraces, utilization, and management of bamboos among rural people of Sukamenak Village, Sumedang of West Java. The method used in this study was mixed-method, a combination of qualitative and quantitative with an ethnobotanical approach. Some techniques, including observation and in-depth interviews with competent informants were employed. Data analysis was carried out by cross-checking, summarizing and synthesizing, and building up narrative. The results showed that 9 bamboo landraces were recorded in Sukamenak Village. The nine landraces of bamboo are classified by local people according to the morphology and color of the internode, edible and non-edible shoots, and their ecological functions in the rural ecosystem. The landraces of bamboo are commonly used by rural people for economic, social and ecological purposes. The utilization and management of bamboo gardens are undertaken by rural people based on local knowledge and are strongly embedded with local culture. We suggest the further studies on bamboo ethnoecology need to be continued due to bamboos have various socio-economic, cultural and ecological functions.